2016
DOI: 10.1088/0031-9155/61/19/7113
|View full text |Cite
|
Sign up to set email alerts
|

Delay grid multiplexing: simple time-based multiplexing and readout method for silicon photomultipliers

Abstract: In this paper, we propose a fully time-based multiplexing and readout method that uses the principle of the global positioning system. Time-based multiplexing allows simplifying the multiplexing circuits where the only innate traces that connect the signal pins of the silicon photomultiplier (SiPM) channels to the readout channels are used as the multiplexing circuit. Every SiPM channel is connected to the delay grid that consists of the traces on a printed circuit board, and the inherent transit times from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Compact and affordable digitizers with sampling rates >1 GHz exist that facilitate multichannel implementation of this approach (Cho et al 2011, Ronzhin et al 2013, Ashmanskas et al 2014, Park et al 2018. Time-multiplexing can be used to reduce costs, but leads to an increased DCR on the multiplexed channel (Grant and Levin 2015, Kim et al 2016, Bieniosek et al 2016a, Won et al 2016a. At the time of writing, waveform sampling of individual events is mostly used in research setups.…”
Section: P1mentioning
confidence: 99%
“…Compact and affordable digitizers with sampling rates >1 GHz exist that facilitate multichannel implementation of this approach (Cho et al 2011, Ronzhin et al 2013, Ashmanskas et al 2014, Park et al 2018. Time-multiplexing can be used to reduce costs, but leads to an increased DCR on the multiplexed channel (Grant and Levin 2015, Kim et al 2016, Bieniosek et al 2016a, Won et al 2016a. At the time of writing, waveform sampling of individual events is mostly used in research setups.…”
Section: P1mentioning
confidence: 99%
“…However, the resulting performance of TOT suffers from a distortion in the energy spectrum degrading energy resolution because of nonlinear input energy to output pulse width conversion. [7][8][9][10][11][12][13][14][15][16][17] MVT is also a digital sampling method, analogous to TOT, to generate samples of an event waveform of PET but employs multiple thresholds to extract energy and time information of a PET event. This method showed that implementing TOT with multiple triggering thresholds could overcome the problems inherent to nonlinear performance of TOT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared with other digital sampling methods, such as DRS and TOT, MVT can provide high performance because it has shorter conversion time for storing amplitudes than DRS achieving high count rate and can obtain more samples per detector output pulse than TOT method improving nonlinearity of energy resolution. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] For design of PET systems using digital sampling methods, such as TOT, DRS, and MVT, a digital DAQ system usually has been employed. These systems consist of an analog-to-digital converter (ADC), time-to-digital converter (TDC), and field-programmable-gate-array (FPGA) for extracting energy and timing information for a detected event.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations